SYUROâ SYSTEM â IN THE ORGANIZATION OF THE ISLAMIC - Imran, Muhammad (Jurnal IUS, 2015)
Syuroâ have meaning discussion to solve a problem. I. In the reign of Islam (Even Islamiyah) Syuroâ is an ideal system in administering Islamic Government in accordance with the law essentially i.e. the Qurâan and Al-Hadith.Â During the reign of Khulafa Rashideen Ur Syuroâ is the ideal cornerstone in determining a leader (Caliph), so also in the process of Division of power as well as other governmental processes.Â In the SyuroâÂ System also known power-sharing terms, before the concept of Trias Political Islamic Government had been born knowing and applying the concept of power-sharing. The Islamic Government in the Executive term known as Tanfidziyah, this institution was occupied by the Caliph, and the legislature is known by the term Tasyriâiyah the Agency is occupied by the SyuroâÂ Council â while the Qaadi or judges are in the position of the judiciary which is known by the term Qadaâiyah. In the implementation of the SyuroâÂ System â the reign of Islam also have one institution in a canal with Ahl Halli Wal Aqdhi i.e. the Group of scholars â who has the right lifting the Caliph and could also depose him based on the provisions of the Shariâah.Keywords: Syuroâ Ideal of the Islamic Foundation in the reign